Active populations and growth of soil microorganisms are framed by mean annual precipitation in three California annual grasslands. (February 2023) - Foley, Megan M.; Blazewicz, Steven J.; McFarlane, Karis J.; Greenlon, Alex; Hayer, Michaela; Kimbrel, Jeffrey A.; Koch, Benjamin J.; Monsaint-Queeney, Victoria L.; Morrison, Keith; Morrissey, Ember; Hungate, Bruce A.; Pett-Ridge, Jennifer
Abstract: Climate influences soil microbial composition and function, but the relative importance of a site's historic climate versus its more immediate environmental conditions is unclear. Using quantitative stable isotope probing (qSIP), we characterized actively growing soil microbial communities and soil properties in three California annual grasslands that span a rainfall gradient and have developed on similar parent material. The soils were assayed in the wet winter season, when environmental conditions are most similar across sites. Since growing populations might be expected to be most responsive to contemporary environmental conditions, we hypothesized that the structure of growing microbial communities would be more similar across the gradient than that of total communities (i.e., including non-growing populations). In addition, we hypothesized that population growth rates would be slowest in the driest site, reflecting a legacy effect of low soil moisture on microbial growth. Soils along the rainfall gradient differed in pH, texture, and cation exchange capacity, but not in total C, C:N or dominant minerals. The radiocarbon ( 14 C) age of soil C (reflecting turnover time) increased with mean annual precipitation but soil respiration was uniformly modern, reflecting microbial reliance on recent C inputs across the sites. The structure of both total and growing microbial communities differed across sites. Across major microbial phyla, including the Actinobacteria, Acidobacteria, Bacteroidetes, Gemmatimonadetes and Proteobacteria, bacterial growth rates were consistently lower in the site with the lowest mean annual precipitation. Taxa that were growing at the dry site alone grew more slowly than taxa that grew at multiple sites. These results reflect the influence of climate history and point to the role of environmental filtering at the driest site in shaping its slower growing microbial community, possibly reflecting adaptation to repeated exposure to water stress. Lastly, across taxa, the growth rate of a taxon at one site was correlated with its growth rate in the other sites. This growth rate coherence is likely a consequence of genetically determined physiological traits and is consistent with the idea that evolutionary history constrains growth rate. Highlights: Climate strongly influences structure of growing soil microbial communities. Repeated low water exposure reduces soil microbial growth across taxonomic levels. Microbial growth rates are consistent between sites across a precipitation gradient. Genetics and physiology constrain variation in taxon-specific growth rates.